The impact behavior of the crash boxes. Issue 1 (December 2020) - Manea, A M; Iozsa, D; Stan, C
Abstract: This article will study the impact behavior of the crash box structures. The crash boxes are found between the front cross member and the front side members. They play an important role in case of minor frontal impact, speeds up to 15km/h. For this study, we propose three models of crash boxes of different sections. The impact analysis will be performed using the software ANSYS, Explicit Dynamics module. The shape and dimensions of the models were obtained from repeated impact tests. Thus, the obtained results were used for the continuous improvement of the crash boxes. The proposed models are made from extruded Aluminum bars with different sections. With the help of finite element analysis (FEM) one can compare the results and what impact energy absorption characteristics each proposed model of structure presents.